Studi Resiliensi Pada Mahasiswi Penyintas Kekerasan - Ghiffari, Muhammad; Adriansyah, Muhammad Ali (Psikoborneo: Jurnal Ilmiah Psikologi, 2022)
This study looked at how survivors are able to become resilience after experiencing violence, based on the traits they display. Four female survivors were selected using a random sampling method, which was based on criteria determined using the screening method. This type of research is qualitative, using phenomenological analysis. The data collection method used is an interview using semi-directed interview techniques that are in accordance with the interview guidelines compiled by the researcher and developed during the interview. The data analysis techniques used are preparing data, reading the entire data, coding data, applying the results of data coding to the topic to be analyzed, presenting the topic in the form of a narrative, and interpreting the data. In the results of research on the subject of female students survivors of violence, with the results of the subject having the ability to regulate self-emotions including the subject of regulating emotions, the ability to control impulses including subjects who are able to control desires, the ability to optimism includes positive thinking in their situation, the ability to find out the source of the problem includes subjects who are able to know the cause of the incident, the ability to self-efficacy includes the desire in the subject to complete  the problem is, empathy ability includes subjects who feel what others feel, and achievement abilities include subjects who are able to achieve what they want and overcome fears in their lives. Penelitian ini melihat bagaimana survivor mampu menjadi resiliensi setelah mengalami kekerasan, berdasarkan sifat-sifat yang mereka tampilkan. Empat perempuan penyintas dipilih menggunakan metode random sampling, yang didasarkan pada kriteria yang ditentukan menggunakan metode skrining. Jenis penelitian ini adalah kualitatif, dengan menggunakan analisis fenomenologi. Metode pengumpulan data yang digunakan adalah wawancara dengan menggunakan teknik wawancara semi terarah yang sesuai dengan pedoman wawancara yang disusun oleh peneliti dan dikembangkan selama wawancara.Teknik analisis data yang digunakan adalah menyiapkan data, membaca seluruh data, mengkodekan data, menerapkan hasil pengkodean data pada topik yang akan dianalisis, menyajikan topik dalam bentuk narasi, dan menginterpretasikan data. Pada hasil penelitian pada subjek mahasiswi penyintas kekerasan, dengan hasil subjek memiliki kemampuan regulasi emosi diri meliputi subjek mengatur emosi, kemampuan pengendalian impuls meliputi subjek yang mampu mengendalikan hasrat, kemampuan optimisme meliputi pemikiran yang positif pada situasi mereka, kemampuan mencari tahu sumber masalah meliputi subjek yang mampu mengetahui penyebab dari kejadian tersebut, kemampuan efikasi diri meliputi keinginan dalam diri subjek untuk menyelesaikan masalahnya, kemampuan empati meliputi subjek yang merasakan apa yang orang lain rasakan, dan kemampuan pencapaian meliputi subjek yang mampu meraih apa yang dinginkan dan mengatasi ketakutan dalam hidupnya.